STUDENTS"™ ATTITUDES TOWARD TEACHING STRATEGIES OF NATIVE AND NON-NATIVE ENGLISH TEACHERS - Syahdan, Shevia Chairul; Hadi, Muhammad Sofian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was aimed to find out similarities of teaching strategies employed by native and non-native teachers of English and to see students"™ attitudes toward those teaching strategies. There were 1 native teacher, 1 non-native teacher and 30 students of grade 8 of SMP Al-Zahra, Pamulang, Tangerang Selatan, participated as research respondents. This research applied qualitative method with case study research design. In gathering the data, the writers administered interview to the two teachers related to teaching strategies they used and distributed a 5-likert scale questionnaire to the students regarding their attitudes to teaching strategies used by the teachers. The data of the interview were analyzed by using thematic analysis, while the results of students"™ responses to the questionnaire were analyzed through triangulation technique. The analysis data revealed that there were several similarities in teaching strategies employed by both teachers, i.e., group discussions, interactive activities, media and real-life scenarios. While the students showed "˜neutral"™ attitudes toward teaching strategies applied by the teachers.